Spring 1865 : the closing campaigns of the Civil War - Jamieson, Perry D. (Lincoln ; London : University of Nebraska Press, 2015)
Perry D. Jamieson juxtaposes for the first time the major campaign against Lee that ended at Appomattox and Gen. William T. Sherman's march north through the Carolinas, which culminated in Gen. Joseph E. Johnston's surrender at Bennett Place. Jamieson also addresses the efforts required to put down armed resistance in the Deep South and the Trans-Mississippi. As both sides fought for political goals following Lee's surrender, these campaigns had significant consequences for the political-military context that shaped the end of the war as well as Reconstruction.
Terrible times of shipwreck -- Fort Fisher and Wilmington -- In the Carolinas -- Bentonville -- Late winter at Petersburg -- The fall of Petersburg -- To Sailor's Creek -- Spring morning -- A scrap of paper -- Scattered embers.
Includes bibliographical references and index.
Keywords: 1861 - 1865; Military campaigns; Peace; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Peace; United States; History